Digital image processing of remote sensing data in Malaysia - Hashim, Mazlan; Ibrahim, Ab. Latif; Abd. Rahman, Muhammad Zulkarnain (2004)
Remote sensing systems now allow image been captured at ranges of electromagnetic spectrum beyond the range of photography. The development of active remote sensing systems, which enable it to function in all weather conditions, had shown a more promising development in the application of this technology. Digital image processing and image enhancement techniques provide recognition of contrasts among features of interests at orders of magnitude better than human eye. Looking at the current global scenario, operational application of remote sensing technology is becoming a common practice and well accepted at operational level in assisting decision making process in the natural resource management, environmental, conservation program and strategic planning. Remote sensing images (and information extracted from such images) are now beginning to be used extensively to locate specific features and conditions of the earth surface. The main objective of this paper is to highlight work on digital image processing in Malaysia as a whole, and also to highlight some of the work that have been carried out at the Department of Remote Sensing, Universiti Teknologi Malaysia. As digital image processing involved various procedures that may be quite complicated, the first part of this paper provide a brief description on the general term of digital image processing, while the focus of the second part of this paperi digital image processing work that have been cariied out in Malaysia and also at Universiti Teknologi Malaysia